2002
DOI: 10.1100/tsw.2002.84
|View full text |Cite
|
Sign up to set email alerts
|

A Throughfall Collection Method Using Mixed Bed Ion Exchange Resin Columns

Abstract: Measurement of ionic deposition in throughfall is a widely used method for measuring deposition inputs to the forest floor. Many studies have been published, providing a large database of throughfall deposition inputs to forests. However, throughfall collection and analysis is labor intensive and expensive because of the large number of replicate collectors needed and because sample collection and chemical analyses are required on a stochastic precipitation event-based schedule. Therefore we developed and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
1
39
1
2
Order By: Relevance
“…[12,13] Pseudomonas aureofaciens was initially used in seawater to study nitrogen cycling in marine ecosystems, [14,15] suggesting that high salt concentrations should not affect the method. Standard reagent grade KCl has a label purity of 99-100.5% KCl.…”
Section: Rationalementioning
confidence: 99%
“…[12,13] Pseudomonas aureofaciens was initially used in seawater to study nitrogen cycling in marine ecosystems, [14,15] suggesting that high salt concentrations should not affect the method. Standard reagent grade KCl has a label purity of 99-100.5% KCl.…”
Section: Rationalementioning
confidence: 99%
“…29 Fenn e colaboradores propuseram modificações no coletor de deposição total pela substituição do frasco coletor por coluna de plástico contendo mistura de resinas de troca iônica (Amberlite IRN 150) para a determinação específica de nitrogênio inorgânico (NH 4 + e NO 3 -). 30 Essa técnica apresenta as seguintes vantagens em relação ao coletor convencional: a) menor frequência de coleta por permitir maior período de exposição; b) maior estabilidade química da espécie de interesse durante a amostragem. 30 …”
unclassified
“…30 Essa técnica apresenta as seguintes vantagens em relação ao coletor convencional: a) menor frequência de coleta por permitir maior período de exposição; b) maior estabilidade química da espécie de interesse durante a amostragem. 30 …”
unclassified
“…Many literature studies have shown that the concentration of N deposition in water N loads has increased [8][9][10], and the ecological effects of atmospheric N deposition have received a great deal of attention in recent years [11,12]. Many methods have been employed to collect N deposition, including ion-exchange resin, micrometeorological integral total N input, and minusing methods [13][14][15][16]. Due to the rapid population growth, industrialization, vehicle ownership, and fossil fuel combustion, the NO x emissions in China have shown a marked increase of 2.8 times from 1980 to 2003 [17,18].…”
Section: Introductionmentioning
confidence: 99%